The association between whole blood viscosity and CHA2DS2-VASc/CHA2DS2-VA scores in patients with atrial fibrillation - Erkan Kahraman; Koray Kalenderoglu (Future Science OA)
Introduction CHA2DS2-VASc and CHA2DS2-VA scores are often used to demonstrate thromboembolic risk in nonvalvular atrial fibrillation. Elevated whole blood viscosity is an independent risk factor for ischemic stroke.Objective This study aimed to ascertain the correlation between whole blood viscosity and CHA2DS2-VASc/CHA2DS2-VA scores.Methods This study was performed retrospectively in a tertiary cardiac facility, encompassing 150 patients.Results The study’s results demonstrate that whole blood viscosity, concerning both high shear rate and low shear rate variables, are statistically significant in forecasting the likelihood of elevated CHA2DS2-VA and CHA2DS2-VASc scores. (AUC: 0.690, 0.693; p: <0.001; 0.647, 0.665; p: <0.05).Conclusion Whole blood viscosity had a substantial correlation with the CHA2DS2-VASc/CHA2DS2-VA scores in patients with atrial fibrillation and may be used to evaluate thromboembolism risk, akin to these scores.